Design and simulation of point absorber wave energy converter - Singh Devesh (EDP Sciences, 2021)
The paper aims to design and simulation of a wave energy harvesting system commonly known as point absorber for Ennore port located in the coastal area of Chennai, India. The geographical condition of India, which is surrounded by the three sides with seas and ocean, has enormous opportunity for power production through wave energy harvesting system. The wave energy converter device is a two-body floating system and its both parts are connected by power take-off unit which acts as spring mass damper system. In this paper, the hydrodynamic diffraction, stability analysis, frequency, and time response analysis is carried out on ansys-aqwa. The numerical results are compared with the results obtained from the similar experiments for validation of CFD solver. Effects of the properties featuring wave characteristics including wave height and wave period of Ennore port on the energy conversion, Froude-Krylov and diffraction force, response amplitude operator (RAO) are studied. Based on the study, float diameter, draft, geometry, and varying damping coefficient for power generation are optimized. Finally, the optimally designed point absorber is simulated as per Indian ocean energy harvesting standard and mass of the system, heave dimension, diffraction forces, and pressure variations are computed.